Pengaruh Gaya Kepemimpinan, Beban Kerja, Dan Insentif Terhadap Kinerja Karyawan Pada CV Gemilang Abadi Semarang - Avilia Moza Pramesti; Wachid Fuady R (Jurnal Ekonomi Manajemen Akuntansi, 2022)
This study aims to analyze "The Influence of Leadership Style, Workload, and Incentives on Employee Performance at CV Gemilang Abadi Semarang." Methods of data collection using a questionnaire. The sampling technique used random sampling technique. A sample of 82 respondents were employees at CV Gemilang Abadi Semarang. Based on the results of the study, leadership style has a positive effect on employee performance. This is shown by the value of t count is greater than t table, namely 3.632 > 1.664, with a sig value. of 0.001 <0.05. Leadership style (β1) has a positive sign of 0.266 which means that the better the leadership style, the higher the employee performance. Thus it can be concluded that H1 is accepted, so the hypothesis stating that leadership style has a positive effect on employee performance is proven. Workload has a positive effect on employee performance. This is shown by the t-value that is greater than the t-table, namely 3.941 > 1.664, with a sig. By 0.000 > 0.05. Workload (β2) has a positive sign of 0.295 which means that the more appropriate the workload is, the better the employee's performance. Thus it can be concluded that H2 is accepted, so the hypothesis stating that workload has a positive effect on employee performance is proven. Incentives have a positive effect on employee performance. This is shown by the greater t-count value of t-table, namely 8.699 > 1.664, with a sig. 0.000 < 0.05. Incentives (β3) have a positive sign of 0.590 which means that the higher the incentives given, the higher the employee's performance. Thus it can be concluded that H3 is accepted, so the hypothesis stating that incentives have a positive effect on employee performance is proven.